Proposals for a National Health Service - Great Britain. National Health Service
1946-01 1946 1940s 16 pages Family Practitioner Services 27. This part of the service will cover general medical care by a personal, or family, doctor of the patient's own choice, with necessary medicines, drugs and appliances, and general dental care, which will be developed as fast as the supply of dentists allows. There will be priority dental provision from the outset, however, for mothers and children (para. 16 above). 28. A principal objective from the outset, in the general medical and the general dental services, will be the development of the health centre system, equipping the practitioner with publicly provided premises, apparatus and ancillary staff. 29. The health centre system will be supplemented by arrangements with doctors in separate practice to join in the service from their own surgeries, so that everyone can be assured of a family doctor from the outset. For dentistry, this assurance may not be possible until more practitioners are available, but during the development of the health centre system arrangements will be made to supplement it by ensuring that any patient treated under the service by individual dentists receives his treatment and necessary appliances at the cost of the service. Local Executive Councils 30. There will be a new system of local Executive Councils for the family practitioner services. There will be a Council for each county and county borough (i.e. local health authority) area, but with power to the Minister to combine two or more areas under one Council, wherever desirable. Each Council will have a chairman, appointed by the Minister, and one half of its members will represent the "consumer" interest, the public, while the other half represents the professions providing the service - doctors, dentists and chemists. Of the public representatives, two-thirds will be nominated by the local health authority of the area, and the other third by the Minister. The professional members will be nominated by representative local professional committees recognised by the Minister for this and other consultative purposes in connection with the family practitioner services. /31. 292/847/4/83